Approach to the empirical conundrum of the use of static stretching in warm-up. (Revista horizonte, 2013)
Traditionally, warm-up includes low-intensity aerobic exercise followed by static stretching. Currently, however, this dogma has been changed. In this brief review will be announced a series of investigations that have shown performance increases and decreases after using different warm-up protocols, manipulating both static and dynamic flexibility. According to the evidence, dynamic flexibility is recommended for activities where power and muscle strength is relevant. Furthermore, static flexibility would not be recommended for this type of activity, but where the range of movement is important.